THE EFFECT OF MOTIVATION, INVESTMENT KNOWLEDGE, FINANCIAL LITERACY ON GENERATION Z INTEREST IN INVESTING IN THE CAPITAL MARKET - Dharmawan Hero Nugroho; Lindiawatie; Dhona Shahreza (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Investment activities in the capital market have attracted the younger generation’s attention, less than 30 years old. They are Generation Z, who were born between 1995 to 2010 and 2012. This research was conducted to determine motivational factors, investment knowledge, and financial literacy on Generation Z’s interest in investing in the capital market. The data collection method was distributing questionnaires to 96 respondents from Generation Z in Jakarta and analyzed using multiple regression analysis. The result is that motivational factors, investment knowledge, and financial literacy significantly and positively affect Generation Z’s interest in investing in the capital market partially and simultaneously. However, the financial literacy factor has a greater influence than the investment knowledge factor. Thus the motivational factor as an internal factor will generate great interest for Generation Z in investing in the capital market if it is supported by external factors in the form of conveying investment knowledge and correct financial literacy. In addition, it will bring changes in attitudes and good financial behavior.